Polyfunctional Energetic Nitrates Derived from Tris(hydroxymethyl)aminomethane (Tris). Issue 25 (5th July 2017) - Klapötke, Thomas M.; Krumm, Burkhard; Reith, Thomas
Abstract : A variety of new energetic compounds were synthesized with the tris(hydroxymethyl)aminomethane (Tris) moiety as a building block. The new nitrates were fully characterized, with use of multinuclear NMR spectroscopy, vibrational analysis, mass spectrometry, differential scanning calorimetry, and elemental analysis. The structure of each compound was confirmed by single‐crystal X‐ray diffraction. The energies of formation were calculated with the Gaussian program package, and the detonation parameters were predicted by using the EXPLO5 computer code. Because of the positive oxygen balance ( Ω CO ) of the presented compounds, their performance data as oxidizers were compared to the common oxidizer ammonium perchlorate. Abstract : Synthesis, full characterization, physical properties, and crystal structures of energetic nitrates based on easily available Tris were determined and investigated. The new energetic materials were compared to the well‐established nitrate pentaerythritol tetranitrate (PETN) and to the oxidizer ammonium perchlorate (AP).